1991
DOI: 10.1055/s-2007-1024734
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Free Radical Scavenger Enzymes in Bicycle Professional Racers. Adaptation to Training

Abstract: This study was designed to investigate the influence of endurance training on the activities of the scavenger enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) measured in erythrocytes from sedentary subjects, amateur bicycle racers and in professional bicycle racers who were cycling in two real cyclist contests including the top-class race Vuelta a España (VCE). Under resting conditions the SOD activity was higher (p less than 0.01) in cyclists than in controls. The activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
3
15

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 7 publications
7
69
3
15
Order By: Relevance
“…In fact, megadoses of vitamins may even impair immune function in athletes (Prasad, 1980). Although the cellular antioxidant mechanism adapts efficiently to acute and chronic exercise (Mena et al, 1991), extreme physical exercise causes oxidative damage to athletes, which is reflected by increases in plasma levels of malondialdehyde (Marzatico et al, 1997), urine 8-hydroxideoxyguanosine (Radak et al, 2000) and erythrocyte catalase activity (Tauler et al, 1999), which could relate to exercise-induced immunodepression. Vitamin C supplementation augmented the increase in lymphocyte counts after exercise (Petersen et al, 2001;Peters et al, 2001b), attenuated the serum cortisol increase in ultramarathon runners (Peters et al, 2001a, b;Nieman et al, 2002b) and attenuated the increases in inflammatory cytokines (Nieman et al, 1997b(Nieman et al, , 2000bPeters et al, 2001a, b), when ingested in doses greater than or equal to 1000 mg/day, but not on 500 mg/day.…”
Section: Antioxidants and Vitaminsmentioning
confidence: 99%
“…In fact, megadoses of vitamins may even impair immune function in athletes (Prasad, 1980). Although the cellular antioxidant mechanism adapts efficiently to acute and chronic exercise (Mena et al, 1991), extreme physical exercise causes oxidative damage to athletes, which is reflected by increases in plasma levels of malondialdehyde (Marzatico et al, 1997), urine 8-hydroxideoxyguanosine (Radak et al, 2000) and erythrocyte catalase activity (Tauler et al, 1999), which could relate to exercise-induced immunodepression. Vitamin C supplementation augmented the increase in lymphocyte counts after exercise (Petersen et al, 2001;Peters et al, 2001b), attenuated the serum cortisol increase in ultramarathon runners (Peters et al, 2001a, b;Nieman et al, 2002b) and attenuated the increases in inflammatory cytokines (Nieman et al, 1997b(Nieman et al, , 2000bPeters et al, 2001a, b), when ingested in doses greater than or equal to 1000 mg/day, but not on 500 mg/day.…”
Section: Antioxidants and Vitaminsmentioning
confidence: 99%
“…Superoxide Dismutase An acute bout of exercise has been shown to increase SOD activity in a number of biological tissues including heart (21,78,99), liver (26,43,74,100,101 ), blood platelets (102), erythrocytes (103), and skeletal muscle (29,74,99,(103)(104)(105). However, reports on the effect of exercise on SOD varies greatly among different studies with many showing no significant effect (see 105 for a review).…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Mena et al 47 showed that highly trained athletes indeed have higher activities of several scavenger enzymes, but the effects of moderate training are apparently much smaller 48 . An increased need for endogenous defence against free radicals might raise the requirements for zinc and copper (in Zn 2 Cu 2 -superoxide dismutase) and selenium (in glutathione peroxidase) in physically active people.…”
Section: Factors Potentially Affecting Micronutrient Requirements In mentioning
confidence: 99%